Pengaruh Company Size, Financial Distress, dan Financial Risk terhadap Financial Reporting Integrity: Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Nurhidayah, Sabilla Putri; Buchori, Willa Putri Malinda (Jurnal Eksplorasi Akuntansi, 2026)
This study aimed to provide empirical evidence on the effect of company size, financial distress, and financial risk on the integrity of financial reports in manufacturing companies listed on the Indonesia Stocks Exchange from 2019 to 2023. This study employed a quantitative descriptive approach, utilizing secondary data in the form of annual reports. The research subjects comprised manufacturing companies listed on the Indonesias Stocke Exchange. A purposive sampling technique was applied, resulting in a dataset of 199. Data analysis methods included observation techniques, descriptive statistics, classical assumption testing, and multiple linear regression analysis. The findings of this study indicated that company size had a positive and significant effect on the integrity of financial statements. This effect was shown by a t-test significances value of 0.035 at the 0.05 significances level. In contrast, the financial distress variable showed a t-test significance value of 0.058 at the 0.05 significance level. The financial risk variable demonstrated a t-test significance value of 0.308 at the 0.05 significance level. These results suggest that while company size affects the reliability of financial reporting, financial distress and financial risk do not have a significant impact. It is recommended that companies use these findings as evaluation material to enhance the accuracy and integrity of their financial reports.